PATH ANALYSIS OF THE RELATIONSHIPS BETWEEN FRUIT YIELD AND SOME YIELD COMPONENTS IN PAPAYA (Carica papaya Carica papaya L.) - ADITI CHAKRABORTY; SARKAR , SUSHANTA KUMAR; PAUL, AMITAVA (The Bioscan, 2018)
Path analysis was performed on plant and fruit characters of twenty four papaya genotypes grown in a two year field experiment to determine for fruit yield, the direct and indirect effects of the various yield contributing traits. Fruit yield per plant was positively and significantly correlated with plant girth (0.44, 0.43), number of fruits per plant (0.89, 0.89) and average fruit weight (0.59,0.57) at both genotypic and phenotypic levels, respectively. Path analysis showed that canopy spread (N-S), had the highest positive and significant direct effect (1.83) on fruit yield followed by days to first flowering (1.40), number of fruits per plant (0.94), plant height (0.50) and average fruit weight (0.46). The significant positive correlation coefficients of number of fruits per plant and average fruit weight with fruit yield were resulted mainly from high and positive direct effects of these traits with fruit yield suggesting direct selection would be rewarding whereas for the character days to first flowering for which correlation coefficient was negative (0.02,0.02) but the direct effect was positive and significant, a restricted simultaneous selection model is to be followed. For the character like plant girth, the indirect causal factors are to be considered simultaneously for selection.